Geography Interactive Learning Media Based on the Articulate Storyline 3 Application to Improve Learning Outcomes in Senior High School - Norsidi Norsidi; Agus Suwarno; Afzal Sayed Munna (Universitas Negeri Gorontalo, 2024)
The use of interactive learning media is increasingly demanded in Geography learning. However, the availability of interactive geography learning media that meets eligibility standards is still limited. This research aims to produce interactive Articulate Storyline 3 media that meets feasibility standards and is validated. Media development refers to the Borg and Gall model. The data collection techniques used were observation, interviews, indirect communication and documentary studies. The data collection tools used were observation guides, interview guides, validation sheets, and documentation. Product trials were carried out in class X of SMA Negeri 2 Simpang Hilir. The data analysis techniques in this research are needs analysis techniques, qualitative and quantitative. The results of the research show that, namely, 1) producing interactive learning media based on Articulate Storyline 3 is suitable for use in the learning process in geography subjects regarding geosphere phenomena; 2) Interactive learning media based on Articulate Storyline 3 is included in the criteria of being very valid and very suitable for use in the learning process which is observed through evaluation by media experts and material experts as well as product trials and usage trials; 3) there are differences in learning outcomes for class XA students at SMA Negeri 2 Simpang Hilir before and after being given interactive learning media based on Articulate Storyline 3, so it is very effective in improving student learning outcomes